Assessment of Toxicological Effects of Triclosan on Microbes, Plants, and Genetic Material in Cells - Sipahutar, Merry Krisdawati (Indonesian Journal of Environmental Management and Sustainability, 2023)
Triclosan is an antiseptic ingredient that is commonly found in numerous personal care items that may end up in the environment. Their ecotoxicological profile, however, is still unknown. The current research aims to determine the toxicity of triclosan on E. coli, Vigna radiata and Crotalaria juncea seeds, and Allium cepa roots. The analyses include toxicity assays for microbes, phytotoxicity, and cytogenotoxicity. The results proposed if the triclosan tested (60-150 µM) became exceedingly harmful to the test bacterium, as seen by the decrease in E. coli CFU, indicated that triclosan had antibacterial properties and inhibited the test microbe, depending on the concentration of triclosan used. Triclosan at concentrations of 40 and 80 µM, respectively, decreased the sprouting length of Vigna radiata and Crotalaria juncea by 45-50% and 70-72%, respectively. Thus, the cytogenotoxicity assay using Allium cepa revealed that triclosan damages the meristematic cells. Triclosan at 40 µM concentration resulted in a 1.2% aberration index and a 10.4% mitotic index, and 80 µM caused a 1.4% aberration index and an 8.8% mitotic index. All of the findings point to triclosan being potentially hazardous to the biota.